1977
DOI: 10.1002/hlca.19770600522
|View full text |Cite
|
Sign up to set email alerts
|

Contribution à l'étude du comportement de la catéchine en milieu alcalin

Abstract: Contribution to the study of the behaviour of catechin in alkaline medium SummaryWhen catechin (1) is warmed with aqueous alkali it first undergoes rapid epimerisation. After some time a novel bridged carbocyclic enol, catechinic acid (3) separates out and may be isolated in excellent yield. Eventually catechinic acid isomerises to 2-(3', 4'-dihydroxyphenyl)-3,9-epoxy-6-oxo-bicyclo[3,3,l]-non-7-en-8,9diol (4) via an open chain anion (5) which is also involved in the epimerisation of catechin. Assignments of st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
3
0

Year Published

1977
1977
2010
2010

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 19 publications
2
3
0
Order By: Relevance
“…Taking all of these data into consideration, the reaction pathways leading to the formation of the flavan-3-ol-Cglycosides by a previously not reported nonenzymatic Cglycosylation of flavan-3-ols are proposed in Figure 6. Under alkaline conditions, (-)-epicatechin ( 1) is epimerized to (-)catechin (2), thus confirming earlier reports (9). As exemplified for the formation of the C-glycoside 6 in Figure 6, the carbonyl atom of the open-chain form of the hexose (3) favorably formed under alkaline conditions ( 13) is attacked by the A-ring of the (-)-epicatechin at the 6-position to give the intermediate adduct 4.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…Taking all of these data into consideration, the reaction pathways leading to the formation of the flavan-3-ol-Cglycosides by a previously not reported nonenzymatic Cglycosylation of flavan-3-ols are proposed in Figure 6. Under alkaline conditions, (-)-epicatechin ( 1) is epimerized to (-)catechin (2), thus confirming earlier reports (9). As exemplified for the formation of the C-glycoside 6 in Figure 6, the carbonyl atom of the open-chain form of the hexose (3) favorably formed under alkaline conditions ( 13) is attacked by the A-ring of the (-)-epicatechin at the 6-position to give the intermediate adduct 4.…”
Section: Resultssupporting
confidence: 90%
“…After 10, 20, 40, and 60 min, the alkalization process was stopped by acidification with hydrochloric acid and, after membrane filtration, aliquots of the mixture were analyzed by means of RP-HPLC coupled to a diode array detector and a mass spectrometer, respectively. First, the model alkalization experiments revealed a significant epimerization of (-)-epicatechin into (-)-catechin, thus confirming earlier data reported in the literature (9). Second, a series of compounds exhibiting a molecular mass of 452 Da was detectable.…”
Section: Resultssupporting
confidence: 88%
“…-EC isomerizes to its corresponding epimer or racemic compounds by thermal treatment exceeding 100°C. ll ,12) Courbat 13 ) reported that a rapid epimerization of catechins occurred in alkaline solution, and Nakagawa 14) pointed out that the isomerization of catechins in the roasting process of green tea was not racemization but epimerization due to the stereochemical configuration of 3-hydroxyfuravanon.…”
Section: Resultsmentioning
confidence: 97%
“…Catechin C ‐glycosides were prepared from (+)‐catechin and α‐ D ‐glucose, α‐ D ‐galactose and α‐ D ‐rhamnose, respectively, in an alkalized aqueous system according to Stark and Hofmann with some modifications 9. Catechin is known to degrade and epimerize fast at high temperatures in an alkaline milieu 26. Thus, the reaction temperature was reduced to 40°C and, to increase the yield, the reaction time was extended up to 120 min.…”
Section: Resultsmentioning
confidence: 99%
“…The formation of the four isomers each time resulted both from epimerization of catechin under alkaline conditions 26, 27 as well as the sugar moiety's ability to be connected to the aglycon at the C‐6 or C‐8 position 28. The mechanism of epimerization is not completely known up to date.…”
Section: Resultsmentioning
confidence: 99%